A changing environment of urban education: historical and spatial analysis of private supplementary tutoring in China. (April 2021) - Zhang, Wei; Bray, Mark
Recent decades have brought dramatic urbanization to China. Between 1978 and 2018, the urban population rose from 17.9 per cent to 59.6 per cent of the total. Urbanization has many implications, including for education. China's government has long been concerned about imbalances in access to and quality of schooling, and new imbalances have been introduced through market forces in the so-called shadow education sector of private supplementary tutoring, arising from both demand and supply. Urban families in particular seek private supplementary tutoring, and tutorial companies favour densely populated areas for higher enrolments. China has the world's largest school system and most extensive shadow provision. This paper conceptualizes the space of shadow provision in educational, social and geographical terms. It highlights the changing scale and nature of private tutoring, observes the roles of new technologies and government regulations, notes the impact of COVID-19, and argues that shadow education both shapes and is shaped by urbanization.